Manufacture and Characterization of PVA-Enzyme/GA/PANI-HCl or PANI-p-toluentsulfonate/PVC-KTpClPB-o-NPOE Indicator Electrode Membranes, Analysis, XRD, SEM-EDX and FTIR - Abd Hakim S (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims at the synthesis and characterization of indicator electrode membranes consisting of PVA-Enzyme/GA/PANI/PVC-KTpClPB-o-NPOE, urea analyte. PANI-HCl and PANI-p-toluensulfonate conducting polymers, 61% and 66% o-NPOE plasticizer variations in PVC-KTpClPB, as well as urease enzyme activity in one or three drops of 0.5 mL PVA (50% water: 50% ethanol). The biosensor potentiometric method was used with the technique of immobilizing the urea enzyme which is the urea analyte. The multi-membrane indicator electrode is PVA-Enzyme/GA/PANI/PVC-KTpClPB-o-NPOE, PANI dissolved in HCl and p-toluensulfonic acid respectively at a concentration of 6 M and 2 M. Each membrane on the indicator electrode is coated with one time. Results of XRD analysis of the spectrum pattern of the PANI-HCl indicator electrode with intensities of 4400 a.u, 1386 a.u, 1724 a.u with a 2theta angle of 28.6 degrees, PANI-p-toluensulfonate with intensities of 10940 a.u, 9194 a.u, 5312 a.u with a 2theta angle of 18.2 degrees. SEM-EDX analysis showed differences in the morphology of the o-NPOE plasticizer of 61% and 66% as well as an increase in cps/eV from the number of drops of the urease enzyme, one drop was lower than three drops. FTIR analysis shows an increase in transmittance by PANI towards PPy. Analysis of the properties of a multi-membrane indicator electrode with one layer of the best sample is PANI-p-toluensulfonate